Failure rate in skin grafts in burn patients and related factors - Fernandes, Marcos Rassi (2023)
Objective: To estimate the failure rate of skin grafts in patients with burns and related factors. Method: This is a quantitative, longitudinal, prospective cohort study, carried out with burn victims undergoing skin grafting. Data collection was performed through interviews, analysis of medical records and evaluation of grafts. Results: The mean follow-up time was 20.7 days. In the sample studied, 41.67% of the patients had failed to adhere to skin grafting and the factors that proved to be significant for success were: change in serum albumin levels; presence of bleeding; presence, amount and appearance of exudate and presence of odor. Conclusion: It can be seen that aspects related to the conditions of the wound bed are decisive in the success of the skin graft.